2015
DOI: 10.1177/1099636215577348
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical investigation of the effect of asymmetry on the residual strength of a composite sandwich panel

Abstract: Asymmetric sandwich panels with skins of differing thickness are subjected to various degrees of damage via quasi-static indentation before compressive loading to failure. These are compared with panels with skins of equal thickness. The experiments show that the asymmetric panels experience an improvement in strength with small amounts of indentation compared with undamaged asymmetric panels, and for more severe damage, show greater residual strength than the symmetric panels. The two configurations are numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The first called CAI-sandwich (CAI-SW) is commonly used in damage tolerance research studies, e.g. [5,7,17,18]. In the CAI-SW experiment quasi-static, uniform, in-plane displacement is applied on the complete cross-section of the sandwich specimen, including both face-sheets and core, as shown in Figure 2.…”
Section: Experimental Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…The first called CAI-sandwich (CAI-SW) is commonly used in damage tolerance research studies, e.g. [5,7,17,18]. In the CAI-SW experiment quasi-static, uniform, in-plane displacement is applied on the complete cross-section of the sandwich specimen, including both face-sheets and core, as shown in Figure 2.…”
Section: Experimental Methodologymentioning
confidence: 99%
“…While assessing the compression after impact (CAI) strength of sandwich structures, Nettles [6] found that normalizing the impact energy with the face-sheet thickness provide reasonable comparison of CAI strength results. James et al [7] studied the effect of asymmetry, i.e. different face thicknesses, on the residual strength of composite sandwich panels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the examined experiments showed that use of elastomeric foam core for the sandwich beams makes a great residual strength in these components after failure of the top skin. The residual strength of the sandwich structures with crushable foam cores after failure is not usually considerable [24,25]. Another advantage of the elastomeric foam cores is recoverability of the deformations, seen in the core instead of permanent deformations which take place in the crushable foams.…”
Section: Sandwich Beams Under 3pb Conditionsmentioning
confidence: 99%
“…In addition to impact, there have been studies that deal with the compressionafter-impact (CAI) behaviour of sandwich panels. The CAI of sandwich panels with damage confined to the face laminates has been extensively investigated in many research works [20][21][22][23][24]. In Shipsha and Zenkert [25], the CAI strength of composite sandwich panels with core crushing damage was studied.…”
Section: Introductionmentioning
confidence: 99%